Persepsi masyarakat lokal terhadap pentingnya hutan dan lahan-lahan lain di lansekap hutan tropis, Kabupaten Malinau, Kalimantan Timur - Liswanti, N. (Bogor Agricultural University, 2004)
This study emphasis on local people perception of the importance of forest and lands, including related attributes, which underlie variations in the type and degree of locally perceived importance. A participatory approach using scoring exercises was completed with seven forest dwelling communities in the tropical landscape of Malinau, East Kalimantan. We also assessed the consistency of this method. The findings suggest that un-logged forest was the most important land category for local people. It provides their livelihoods and well-being both directly and indirectly. 'Forest' has heritage values and contained abundance of valuable and significant plants and animals. In the future, 'forest' is predicted to remain important for local people mainly for timber. Forests are exceptional in comparison with other land types. In addition, the value of forest cases apparently decreases less with distances. However, logged forest is rated as much less important, allowing us to suggest improvements in forest management that better protect local values. Using limited set of scoring exercises, it demonstrates that their consistency can be examined quantitatively as well as qualitatively. This allows it to access new explanations, which give new insights. Logical consistent results are more likely if question are narrowly defined, and if respondents have some education, but even uneducated respondents can provide apparently meaningful and consistent number if care is taken.